A novel semi-active control strategy based on the quantitative feedback theory for a vehicle suspension system with magneto-rheological damper saturation. (October 2018) - Jeyasenthil, R.; Choi, S.B.
Abstract: This paper presents a robust controller for a semi-active suspension system with actuator saturation. It addresses the vehicle vibration attenuation problem under two cases: (i) without actuator fault (magneto-rheological (MR) damper) and (ii) with base oil leakage in MR damper. The solution is obtained using the quantitative feedback theory (QFT) design. The actuator (MR damper) dynamics is well approximated by a first order model with an uncertain time constant. The superior performance of the proposed QFT controller, for fault free case, is compared with the sky-hook, H ∞ control and passive suspension in time as well as in frequency domains. To address the system with faulty MR damper, a multiple model approach based QFT design is then proposed. The multiplicative type fault is considered as an MR damper fault and the faulty damper output delivering capability is then reduced by 80% to 75% due to the oil leakage in the damper. The proposed idea is centered on dividing the large uncertain system into a set of small uncertain linear system and then design the QFT controller corresponding to each of the generated linear models. The global controller is formulated by aggregating the local controller with the gap metric based weights. This new approach produces the similar performance as that of the passive fault tolerant control (FTC)-QFT design with less control effort. Extensive comparative simulations are provided to show the efficacy of the proposed method over passive FTC-QFT, passive FTC- H ∞ design and sky-hook control.